The causal relationship between neuromyelitis optica spectrum disorder and other autoimmune diseases - Wang, Xiaofei; Shi, Ziyan; Zhao, Zhengyang; Chen, Hongxi; Lang, Yanlin; Kong, Lingyao; Lin, Xue; Du, Qin; Wang, Jiancheng; Zhou, Hongyu (Frontiers in Immunology, 2022)
Objectives: The coexisting of neuromyelitis optica spectrum disorder (NMOSD) with other autoimmune diseases has been well recognized. However, the causal association between these two conditions has not been fully studied. The etiology and therapies of NMOSD coexisting with autoimmune diseases also need to be elucidated. Methods: We performed two-sample Mendelian Randomization (MR) analysis to examine the causality. Genome-wide association (GWAS) summary data from NMOSD, autoimmune thyroid disease (AITD), systemic lupus erythematosus (SLE), and sjogren’s syndrome (SS) were used to identify genetic instruments. Causal single-nucleotide polymorphisms (SNPs) were annotated and searched for cis-expression quantitative trait loci (cis-eQTL) data. Pathway enrichment analysis was performed to identify the mechanism of NMOSD coexisting with AITD, SLE, and SS. Potential therapeutic chemicals were searched using the Comparative Toxicogenomics Database. Results: The MR analysis found that AITD, SLE, and SS were causally associated with NMOSD susceptibility, but not vice versa. Gene Ontology (GO) enrichment analysis revealed that MHC class I-related biological processes and interferon-gamma mediated signaling pathway may be involved in the pathogenesis of NMOSD coexisting with AITD, SLE, and SS. A total of 30 chemicals were found which could inhibit the biological function of cis-eQTL genes. Conclusions: Our findings could help better understand the etiology of NMOSD and provide potential therapeutic targets for patients with coexisting conditions.